Revisiting the Importance of History Taking and Clinical Examination in a Postpartum Case! - R Heena Kishore Vaswani; Shilpa Kshirsagar (Journal of Clinical and Diagnostic Research)
Secondary Postpartum Haemorrhage (PPH) is an uncommon but potentially life-threatening complication that occurs between 24 hours and 12 weeks postpartum. Retained Products of Conception (RPOC), a condition in which placental or foetal tissue remains in the uterus following childbirth, miscarriage, or abortion, is one of the leading causes of secondary PPH. Haematological conditions such as Von Willebrand’s disease and thrombocytopenia, choriocarcinoma and infection and dehiscence of the caesarean section scar are some of the rarer causes of secondary PPH. This condition can lead to complications such as abnormal uterine bleeding, infection and endocrine disruptions. Hereby, authors present a case of secondary PPH due to RPOC, in which the patient presented with complaints of intermittent, dull-aching lower abdominal pain and occasional passage of small clots per vaginum. Although the patient was symptomatic, she believed that it was a normal phenomenon to experience irregular vaginal bleeding postdelivery and therefore did not mention it initially. This history was elicited, which further led us to conduct a thorough clinical examination.